Reactions Leading to Controlled Hydrophilicity/Hydrophobicity of Surfaces - Basinska, Teresa (Current Organic Chemistry, 2017)
This review presents recent achievements in manufacturing of supports with controlled hydrophilicity/ hydrophobicity. The broad spectrum of reactions and polymerization processes leading to polymers tethered to surfaces is described. Commonly, brush-like polymers or copolymer layers attached to solid supports constitute the interface between the support and the surroundings. Modification of solid supports by polymer brushes is required to improve or change the attributes of the solid materials and introduce functionalities to modify their properties. For instance, designed polymer supports with appropriate hydrophilicity/ hydrophobicity assure controlled adsorption or covalent immobilization of biomolecules and cells as well as the growth process of cell colonies. Similarly, charge carrier transport occurs across properly developed polymer layers fixed to the metal surfaces of organic electronic devices (sensors, organic light-emitting diodes, and organic photovoltaics). In turn, the development of modern materials requires the application of various controlled polymerization methods and techniques to achieve polymer/copolymer layers with the desired properties and thickness, appropriate hydrophilicity/hydrophobicity balance, and stable attachment to supports. In this paper, attention is focused on the requirements that must be fulfilled to prepare supports and achieve controlled polymerization processes suitable for fabrication of novel materials of various sizes for various applications. Methods tailored for preparing inorganic and organic materials for binding polymer chains are described, as well as procedures for realizing grafting of polymers/copolymers in a variety of arrangements of desired thickness and hydrophilic/hydrophobic balance.
Keywords: hydrophobicity